2014
DOI: 10.1155/2014/171053
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges for Serum Uric Acid among Healthy Assamese People

Abstract: This study was designed to establish reference ranges for serum uric acid among healthy adult Assamese population. Samples from 1470 aged 35–86 years were used to establish age and sex related reference range by the centile method (central 95 percentile) for serum uric acid level. There were 51% (n = 754) males and 49% (n = 716) females; 75.9% (n = 1115) of them were from urban area and the rest 24.1% (n = 355) were from the rural area. Majority of the population were nonvegetarian (98.6%, n = 1450) and only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…For example, Das et al reported that serum UA ranged from 2.6 to 8.2 mg/dL in a healthy Assamese population (27). In the present cohort, UA ranged from 2.4 to 6.2 mg/dL.…”
Section: Discussionsupporting
confidence: 40%
“…For example, Das et al reported that serum UA ranged from 2.6 to 8.2 mg/dL in a healthy Assamese population (27). In the present cohort, UA ranged from 2.4 to 6.2 mg/dL.…”
Section: Discussionsupporting
confidence: 40%
“…Among Koreans, the reported reference level of SUA was 5.37 ± 1.106 mg/dL in men and 3.87 ± 0.745 mg/dL in women, [ 27 ] which seems to be slightly lower compared to those of other Asian countries. [ 28 , 29 ] Those discrepancies may come from nutritional status and other physical conditions. Thus, our results may not be generalizable to other ethnic groups with different demographics.…”
Section: Discussionmentioning
confidence: 99%
“…Because the reference interval is also susceptible to methodological differences, population characteristics and geographical differences, the reference interval provided by the reagent manufacturer has limitations, so a laboratory self-built reference interval is particularly important. 12,13 Unfortunately, so far there have been a few reports about the establishment of SAA reference intervals in humans. 14,15 Hence, the present study was conducted through recruitment, sampling, and measurement.…”
Section: Introductionmentioning
confidence: 99%